Real-time implementation of H.263 video conferencing system using the multimedia video processor (MVP) - Gan, Woon Seng (2008)
This report focuses on isues such as partitioning data in a farm topology, modeling the speedup of the parallel implementation and analysing the scalability of the parallel implementation of the H.263 encoder.